The Effect of Usefulness, Ease of Use, Risk, and Trust to Behavioral Intention in the Use of Internet Banking - Robino Indan; Rio Andika; Muhammad Ridwan; Robby Darma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2016)
Recently information technology is one of the vital elements in human daily activity supports. One example of information technology measurement is based on the Technology Acceptance Model (TAM), which is an information system that shows how users come to accept and use the technology. Usefulness and Ease of Use are the main reasons that would predispose a person to use such technology. The TAM is also applied to the use of Internet Banking, but there are some more factors that will affect the Behavior Intention in using the Internet Banking including Risk and Trust. The aim of this study is to prove the hypothesis of the variables that affect the Behavior Intention. Research variables were measured using a questionnaire that is processed with SPSS software. The results showed that the four variables studied positive influence on Behavior Intention in the use of Internet Banking.